2017
DOI: 10.1002/2016tc004342
|View full text |Cite
|
Sign up to set email alerts
|

Internal deformation of the southeast Levant margin through continued activity of buried mass transport deposits

Abstract: Mass transport deposits (MTDs) are commonly regarded as motionless evidences of past mass wasting events. Three‐dimensional seismic surveys acquired offshore central Israel reveal continued long‐lasting and even current deformation of >1.5 Myr old MTDs, now buried hundreds of meters beneath and still impacting the seafloor. Faulting and folding of the Messinian‐Pliocene unconformity (M), at the base of the studied interval, represent the possible impacts of tectonic and halokinematic deformation. However, an ~… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Leila, Kora, Ahmed, and Ghanem () report of similar lithology of late Messinian age in the Nile Delta. Safadi et al () on the other hand, interpreted a 100–400 m unit overlying and onlapping the IMTS as Nile‐derived sediments prograding northeastwards based on the well data analysis of the Romi‐1 well by Almogi‐Labin et al (). Papadimitriou et al () interpreted post‐IMTS units in the western Levant Basin, around the Eratosthenes Seamount (ESM), as large deep‐sea fans in concordance with Hawie et al (), and assigned chaotic facies unconformably overlying the IMTS as Plio‐Quaternary units representing reworked evaporites or clastic mounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leila, Kora, Ahmed, and Ghanem () report of similar lithology of late Messinian age in the Nile Delta. Safadi et al () on the other hand, interpreted a 100–400 m unit overlying and onlapping the IMTS as Nile‐derived sediments prograding northeastwards based on the well data analysis of the Romi‐1 well by Almogi‐Labin et al (). Papadimitriou et al () interpreted post‐IMTS units in the western Levant Basin, around the Eratosthenes Seamount (ESM), as large deep‐sea fans in concordance with Hawie et al (), and assigned chaotic facies unconformably overlying the IMTS as Plio‐Quaternary units representing reworked evaporites or clastic mounds.…”
Section: Discussionmentioning
confidence: 99%
“…Based on gamma-ray and resistivity logs, Gvirtzman et al (2017) suggest that the unit consist of interbedded halite, anhydrite and clay of latest Messinian age. Other studies have suggested that the strata immediately overlying the intra-Messinian truncation surface (IMTS) consists of nonmarine clastic sediments time equivalent to the Lago Mare phase deposited in fluvio-deltaic systems along the basin margin and/or Nile-derived sediments (Ben-Gai, Ben-Avraham, Buchbinder, & Kendall, 2005;Madof, Bertoni, & Lofi, 2019;Madof & Connell, 2017;Safadi, Meilijson, & Makovsky, 2017;Tibor, Ben-Avraham, Steckler, & Fligelman, 1992). This discrepancy in the interpreted regional stratigraphy is poorly understood, and is either due to a more complex depositional environment than previously believed or, alternatively, erroneous interpretation of the local stratigraphy in parts of the basin.…”
mentioning
confidence: 99%
“…All of the MTDs observed in the study area have extremely flat truncated tops, indicating that they were deposited in zones of sediment bypass and that their tops were eroded and planed off by succeeding flows. Post‐failure deformation of large‐scale MTDs may result in faulting and differential sagging of the overlying undeformed material (Alves & Cartwright, ; Safadi et al ., ). A similar case was documented in small‐scale and meso‐scale MTDs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in segments 1 and 3 and the southern part of segment 4 of the slope, the shelf edge faults are rooted within the upper Pliocene‐Quaternary sediments, and generally, do not reach the M reflection (Figure ). Safadi et al () illustrated the continuous post‐failure deformation of buried MTDs within the area define here as segment‐3, and suggested that these MTDs accommodate a long‐term internal collapse of this section of the continental margin. The faults delineated along the entire length of the shelf edge of segments 1 and 3, expand the range of Safadi et al’s () observations and support the prevalence of their proposed internal deformation mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Safadi et al () illustrated the continuous post‐failure deformation of buried MTDs within the area define here as segment‐3, and suggested that these MTDs accommodate a long‐term internal collapse of this section of the continental margin. The faults delineated along the entire length of the shelf edge of segments 1 and 3, expand the range of Safadi et al’s () observations and support the prevalence of their proposed internal deformation mechanism. We suggest that, away from the Disturbances, internal deformation of the continental margin controls the upper bound of the continental slope at the edge of the shelf.…”
Section: Discussionmentioning
confidence: 96%